The Status of Technology Integration in Music Classrooms and Implications for Technology Training: A Survey of K-12 Music Educators in Four Southeastern States - Lynn M Holliman (Journal of the Association for Technology in Music Instruction, 2022)
This study investigated the status of technology integration in K-12 music classrooms after the onset of Covid-19 across Alabama, Arkansas, Louisiana, and Mississippi. Participants completed an online survey concerning their technology use, comfort levels with technology, training since the onset of Covid-19, and barriers to technology integration. Previous studies in this area showed a slow increase in technology use. Other studies revealed a need for further training of pre-service and in-service educators to integrate technology into their instruction successfully. Results of this survey revealed an increase in technology use and comfort levels with technology specific to distance learning such as recording equipment, video conferencing software, online platforms, interactive websites, and apps for tablet devices after the onset of Covid-19. Respondents most often received training from their school district or through their own independent research. Implications for this study indicate (a) teacher training effectiveness is key for those who need more technological comfort in their teaching, and (b) results of surveys such as this contribute to the continued conversation about the importance of technology training for pre-service and in-service music educators.
Keywords: Technology; Music; Education; Music Education; Covid-19